Key multi(ferrocenyl) complexes in the interplay between electronic coupling and electrostatic interaction. Issue 12 (10th February 2015) - Santi, Saverio; Bisello, Annalisa; Cardena, Roberta; Donoli, Alessandro
Abstract : In this review, the properties of the most significant examples of multi(ferrocenyl) cations containing a number of ferrocenyl units from two to six are discussed and the results are compared with the outcomes of some of our recent studies on conjugated ferrocenyl complexes. Abstract : In this review, the properties of the most significant examples of multi(ferrocenyl) cations containing a number of ferrocenyl units from two to six are discussed and the results are compared with the outcomes of some of our recent studies on conjugated ferrocenyl complexes, in order to give an overview of how the nature of the bridging ligand, the distance between the redox-active centres, and the medium affect the electronic and electrostatic properties of the molecules.